Brain Transcriptome Analysis Links Deficiencies of Stress-Responsive Proteins to the Pathomechanism of Kii ALS/PDC - Satoru Morimoto; Mitsuru Ishikawa; Hirotaka Watanabe; Miho Isoda; Masaki Takao; Shiho Nakamura; Fumiko Ozawa; Yoshifumi Hirokawa; Shigeki Kuzuhara; Hideyuki Okano; Yasumasa Kokubo (MDPI AG, 2020)
Amyotrophic lateral sclerosis and Parkinsonism-dementia complex (ALS/PDC) is a unique endemic neurodegenerative disease, with high-incidence foci in Kii Peninsula, Japan. To gather new insights into the pathological mechanisms underlying Kii ALS/PDC, we performed transcriptome analyses of patient brains. We prepared frozen brains from three individuals without neurodegenerative diseases, three patients with Alzheimer's disease, and 21 patients with Kii ALS/PDC, and then acquired microarray data from cerebral gray and white matter tissues. Microarray results revealed that expression levels of genes associated with heat shock proteins, DNA binding/damage, and senescence were significantly altered in patients with ALS/PDC compared with healthy individuals. The RNA expression pattern observed for ALS-type brains was similar to that of PDC-type brains. Additionally, pathway and network analyses indicated that the molecular mechanism underlying ALS/PDC may be associated with oxidative phosphorylation of mitochondria, ribosomes, and the synaptic vesicle cycle; in particular, upstream regulators of these mechanisms may be found in synapses and during synaptic trafficking. Furthermore, phenotypic differences between ALS-type and PDC-type were observed, based on HLA haplotypes. In conclusion, determining the relationship between stress-responsive proteins, synaptic dysfunction, and the pathogenesis of ALS/PDC in the Kii peninsula may provide new understanding of this mysterious disease.